Agroindustri Gula Semut Aren dengan Model Hariang di Propinsi Banten / Agroindustry of Granular Brown Sugar by Hariang Model in Banten Province - Abner Lay; Steivie Karouw (Pusat Penelitian dan Pengembangan Perkebunan, 2006)
The problems in development of granular brown sugar agrorindustry depend on scale of bussines, tipe of processing and management, so a development model that can give some benefits to farmer grup and the other institution is needed. The research was carried out in Banten Province on July 2005. The research was conducted as survey method and data were collected by Purposive Random Sampling. The data consist of primer and secundair data obtained from farmers/ farmer groups, village cooperative and government institutions, characteristics of neera, crude granular brown sugar and pure granular brown sugar. The data were analyzed by descriptive method. The results showed that agroindustry of granular brown sugar on Hariang Model in Banten Province was managed by village cooperative namely KUB Mandala. Processing of garnular brown sugar was done in farmers groups using traditionally method, the cooperative collected and converted it to pure granular brown sugar. The final product is meet with quality standard and has traded for regional and export market. Agroindustry of granular brown sugar by Hariang Model is classified as innovation technology which suitable to be implemented and has given some positive effect to farmers/farmer groups, diversification of product and extensification of palm sugar (Arenga pinnata) areas. This model can be used for developing of granular brown sugar agroindustry in some places as central production of palm sugar and possible for other commodities adopting in farmer institutional, processing system, management bussines and farmer-investor partnership. RINGKASANPermasalahan pengembangan agroindusri gula semut tergantung pada skala usaha, pola pengolahan dan pengusahaannya, sehingga diperlukan model pengembangan yang menguntungkan kelompok tani. Penelitian di laksanakan pada bulan Juli 2005 di Propinsi Banten. Penelitian menggunakan metode survei dan pengumpulan data secara Purposive Random Sampling. Data yang dikumpulkan terdiri dari data primer dan sekunder. Data primer berasal dari petani, koperasi unit desa, karakteristik nira segar, gula semut kasar dan gula semut, sedangkan data sekunder berasal dari instansi pemerintah. Analisis data dilakukan secara deskriptif. Hasil Penelitian menunjukkan bahwa Agroindustri gula semut Model Hariang di Propinsi Banten, yang dikelola koperasi unit desa dengan nama KUB Mandala. Pengolahan gula semut dilakukan oleh kelompok tani dengan cara tradisional, produk yang dihasilkan petani dalam bentuk gula semut kasar, diolah lebih lanjut oleh unit pengolahan pada koperasi. Produk akhir adalah gula semut yang memenuhi standar mutu dan dipasarkan pada pasar regional dan ekspor. Agroindustri gula semut model hariang dikalsifikasi sebagai teknologi inovasi yang siap diimplementasikan, dan model ini telah memberi pengaruh positif bagi kelompok tani pada pengembangan diversifikasi produk dan intensifikasi tanaman aren. Model ini dapat dikembangkan pada daerah sentra produksi aren dan memungkinkan diadopsi untuk pengembangan komoditas lain dengan penyesuaian terhadap kelembagaan petani, sistem pengolahan, pengelolaan usaha dan kerjasama dengan mitra usaha.